2014
DOI: 10.3390/rs61212187
|View full text |Cite
|
Sign up to set email alerts
|

Improved Wetland Classification Using Eight-Band High Resolution Satellite Imagery and a Hybrid Approach

Abstract: Although remote sensing technology has long been used in wetland inventory and monitoring, the accuracy and detail level of wetland maps derived with moderate resolution imagery and traditional techniques have been limited and often unsatisfactory. We explored and evaluated the utility of a newly launched high-resolution, eight-band satellite system (Worldview-2; WV2) for identifying and classifying freshwater deltaic wetland vegetation and aquatic habitats in the Selenga River Delta of Lake Baikal, Russia, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 45 publications
4
83
0
Order By: Relevance
“…With the improved spatial resolution of remotely sensed imagery, the object-oriented strategy has also been proposed [22][23][24]. However, the accuracy and robustness of the existing classification methods are not yet satisfactory for wetland management, bearing big omission and commission errors due to the sparse yet variable vegetation and the hydrological fluctuation in the wetlands of arid areas [25,26]. The random forest (RF) algorithm, an integrative classifier, has shown to be able to achieve high classification accuracy even when applied to analyze data with stronger noise [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…With the improved spatial resolution of remotely sensed imagery, the object-oriented strategy has also been proposed [22][23][24]. However, the accuracy and robustness of the existing classification methods are not yet satisfactory for wetland management, bearing big omission and commission errors due to the sparse yet variable vegetation and the hydrological fluctuation in the wetlands of arid areas [25,26]. The random forest (RF) algorithm, an integrative classifier, has shown to be able to achieve high classification accuracy even when applied to analyze data with stronger noise [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The classification result and older topographic data were differenced and used to obtain the resulting change layer. Wetlands are one of the most difficult ecosystems to classify due to their high spatial heterogeneity and temporal variability, varying sizes and shapes, diversity of plants species, vegetation structures and types and water levels (Lane et al, 2014). There was no available data for wetlands within the CD: NGI topographic dataset, even though the topographic structure makes provision for this class.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of image texture (Haralick et al 1973;Blaschke et al 2014) can assist with the classification process and has been found to increase classification accuracies (Aguilar et al, 2013;Franklin and Peddle, 1990). The texture measure GLCM (grey level co-occurrence matrix) contrast is effective in differentiating built-up areas from non-built-up areas (Duncan, 2013) and GLCM homogeneity is useful for wetland class discrimination (Lane et al, 2014). …”
Section: Image Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Worldview-2 sensor collects eight spectral bands including the Coastal Blue, Blue, Green, Yellow, Red, Red Edge, Near Infrared 1 (NIR1), and Near Infrared 2 (NIR2). The Coastal Blue, Yellow, Red Edge, and NIR2 spectral bands of Worldview-2 have been shown to increase the accuracy of wetland vegetation classification [17]. This study used Quickbird-2 imagery data acquired on 10 September 2003 and 9 September 2008, and Worldview-2 data acquired on 15 September 2012 and 19 September 2013.…”
Section: Remote Sensing Datamentioning
confidence: 99%